2011
DOI: 10.1073/pnas.1018343108
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of a species-specific translational arrest module to monitor different cellular processes

Abstract: Nascent chain-mediated translation arrest serves as a mechanism of gene regulation. A class of regulatory nascent polypeptides undergoes elongation arrest in manners controlled by the dynamic behavior of the growing chain; Escherichia coli SecM monitors the Sec protein export pathway and Bacillus subtilis MifM monitors the YidC membrane protein integration/folding pathway. We show that MifM and SecM interact with the ribosome in a speciesspecific manner to stall only the ribosome from the homologous species. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
60
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 28 publications
(60 reference statements)
6
60
0
1
Order By: Relevance
“…Although SecM and MifM peptides elicit the same ribosomal response-programmed translation arrest-they do not share any obvious homology. By using a cell-free translation system driven by either E. coli or B. subtilis ribosomes, Chiba et al (1) were able to show that the B. subtilis MifM nascent peptide prompts stalling of the B. subtilis ribosome but not of the foreign E. coli ribosome. Conversely, the SecM nascent peptide, which efficiently arrests progression of the homologous E. coli ribosome, fails to do so when translated by heterologous ribosomes from B. subtilis (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although SecM and MifM peptides elicit the same ribosomal response-programmed translation arrest-they do not share any obvious homology. By using a cell-free translation system driven by either E. coli or B. subtilis ribosomes, Chiba et al (1) were able to show that the B. subtilis MifM nascent peptide prompts stalling of the B. subtilis ribosome but not of the foreign E. coli ribosome. Conversely, the SecM nascent peptide, which efficiently arrests progression of the homologous E. coli ribosome, fails to do so when translated by heterologous ribosomes from B. subtilis (Fig.…”
mentioning
confidence: 99%
“…Chiba et al (1) in this issue of PNAS reveal that, at least in some cases, these dialogues can be species-specific.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although SpoIIIJ and YidC2 share growth-essential functions, as indicated from the synthetic lethal phenotype of their deletion (8,9), SpoIIIJ is constitutively expressed and YidC2 is induced upon dysfunction of SpoIIIJ (10,11) in a manner that is repressible autogenously (12). MifM is encoded from the upstream ORF of yidC2 and plays an essential role in this cross-feedback and autogenous regulation by undergoing regulated elongation arrest in its translation (12)(13)(14). The ribosome stalling at mifM leads to exposure of the ShineDalgarno sequence of yidC2 to enhance its translation.…”
mentioning
confidence: 99%
“…While the ribosome uses wellconserved mechanisms for decoding and peptide bond formation, it also must deal with divergent proteome members in the reviewing process involving the exit tunnel. Shinobu Chiba showed that the MifM arrest sequence acts in a species-specific manner against the B. subtilis ribosome (21,98). It would seem difficult at present to predict which sequences might interact with the exit tunnel/active site regions of the ribosome.…”
Section: Importance Of Late-evolved and Ad Hoc Regulatory Elementsmentioning
confidence: 99%